PEMAKNAAN DAN SIKAP REMAJA PADA BERITA KAMPANYE PILPRES 2019 DI MEDIA SOSIAL - Lestari, Sri Budi (Interaksi: Jurnal Ilmu Komunikasi, 2019)
The development of technology makes the lives of adolescents integrated with social media and digital. Ease of accessing information through digital media, making teens fall into the trap of being over-communicated, and even tends to only share information without being filtered first. How young people interpret news about the 2019 Presidential Election campaign and their attitude to the campaign news they receive is important to watch out for so that young people don't get lost in the rush of information.This research is a qualitative study using a reception analysis approach that aims to find out how teenagers receive and respond to news information on the 2019 Presidential Election campaign on social media. The results inform that the informants already have the ability to see true and untrue news. The informants can already be said to be literate in media and political information even though there are those who say they do not like political news, but during the Presidential and Regional Election in April 2019 they continued to make their choices.